STRATEGIC PERFORMANCE MEASUREMENT SYSTEM (SPMS) FOR THE UNDERWRITING CYCLE IN PT ASURANSI CAKRAWALA PROTEKSI INDONESIA - NICOLAUS PRAWIRO; SUBAGYO (CV KULTURA DIGITAL MEDIA, 2023)
The purpose of this study is to find out the implementation of SPMS in relation to Business Strategy, Competitive Advantage and the underwriting cycle that occurs in the General Insurance Industry where companies carry out their business activities. This research method uses the interview method to employees at the managerial level of PT Asuransi Cakrawala Proteksi Indonesia. Other information data used is taken from company activity records, company websites, print media such as Insurance Media , regulators (Financial Services Authority / OJK), Indonesian General Insurance Association (AAUI), journals published both nationally and internationally, articles in newspapers, libraries, other books that support this research. The General Insurance Industry experiences cycles in setting underwriting policies so that general insurance companies make the underwriting cycle a determining factor in determining company strategy. Insurance companies must be able to read the underwriting cycle that occurs in order to determine the right company strategy to gain competitive advantage in maintaining business resilience and growth. This paper reviews the implementation of the Strategic Performance Measurement System (SPMS) in a general insurance company which is expected to provide input for the company to be better prepared in carrying out business activities in a dynamic industry.